Innovation engineering as the instrument of decision-making support - Kraskevich, V.E.; Selivanova, A.V. (Математичне моделювання в економіці, 2017)
The proposed methods of assessment of the innovation project by way of application of innovation engineering as the information-analytical instrument. Methodology of situation modeling has been used for assessment of the innovation project technological decisions effectiveness.